A COMPREHENSIVE REVIEW OF SURGICAL TREATMENTS FOR INGROWING TOENAILS - Magdalena Kowalczyk,; Karol Bednarz,; Piotr Pitrus,; Anita Krowiak,; Gabriela Majka,; Karolina Krowiak,; Anita Warzocha,; Wiktoria Hander,; Aleksandra Karnas,; Maria Jasiewicz, (International Journal of Innovative Technologies in Social Science, 2025)
Ingrown toenails, also known as onychocryptosis, are a very common condition that affects patients' quality of life due to pain, inflammation, and the risk of infection. While conservative treatment is effective in mild cases, more severe or chronic forms of the condition usually require surgical intervention. Over the years, numerous surgical methods have been developed to improve treatment outcomes, reduce the risk of recurrence, and minimize postoperative complications. This review presents an evaluation of various surgical strategies, analyzing their effectiveness, advantages, disadvantages, and patient outcomes based on current clinical evidence. Ingrown Toenail Before Surgical Treatment: [Clinical Presentation from Private Collection]